Providing Women's Cancer Screening and Education in an Underserved Border Population - Allison Mootz; Andres Belmont De Santiago; Jesus Gutierrez; Kelcy Steffen; Ira Swinney; Maureen Francis (Journal of Student-Run Clinics, 2018)
Health disparities related to breast and cervical cancer screening and mortality exist for Hispanic women living near the United States (US)-Mexico border. The Medical Student Run Clinic (MSRC) at Texas Tech University Health Sciences Center El Paso Paul L. Foster School of Medicine provides free health care to a primarily Hispanic, Spanish-speaking border community and has focused on expanding its women's cancer screening services. The MSRC held mammogram drives, clinical breast exam (CBE) nights, and cervical cancer screenings with the help of student and physician volunteers alongside community health workers. Also, a Women's Health Day Clinic was held, providing CBEs, Pap smears, and women's health education. Clinic volunteers provided 163 women with CBEs, out of which 154 women then received screening mammograms, nine women were referred directly for diagnostic testing, and one patient was diagnosed with breast cancer. For cervical cancer screening, 55 Pap smears were performed. Through its mammogram drives, cervical cancer screenings, and Women's Health Day Clinic initiatives, the MSRC demonstrated a method to increase access to women's preventative health care services in a medically underserved community. The MSRC's women's health initiatives serve as examples for other student-run free clinics on how to implement preventative health screenings and education for their patient populations.